Isotopic partitioning by small mammals in the subnivium. Issue 18 (4th September 2015) - Calandra, Ivan; Labonne, Gaëlle; Mathieu, Olivier; Henttonen, Heikki; Lévêque, Jean; Milloux, Marie‐Jeanne; Renvoisé, Élodie; Montuire, Sophie; Navarro, Nicolas
Abstract In the Arctic, food limitation is one of the driving factors behind small mammal population fluctuations. Active throughout the year, voles and lemmings (arvicoline rodents) are central prey in arctic food webs. Snow cover, however, makes the estimation of their winter diet challenging. We analyzed the isotopic composition of ever‐growing incisors from species of voles and lemmings in northern Finland trapped in the spring and autumn. We found that resources appear to be reasonably partitioned and largely congruent with phylogeny. Our results reveal that winter resource use can be inferred from the tooth isotopic composition of rodents sampled in the spring, when trapping can be conducted, and that resources appear to be partitioned via competition under the snow.